Phytochemical Analysis of Forest Betel Leaves (Piper aduncum L.) Using GC-MS and Antibacterial Activity Against Staphylococcus aureus - Mawo, Yoseph Putra Albertino; Muntasir, Muntasir; Purnasari, Cahyani; Dean, Muhajirin (Jurnal Biologi Tropis, 2026)
Skin infections due to Staphylococcus aureus continue to be a major health issue, particularly with the increase in antibiotic resistance. Traditionally, forest betel leaves (Piper aduncum L.) have been utilized for treating wounds and skin ailments. The goal of this research is to explore the chemical components of a 95% ethanol extract of Piper aduncum L. leaves through GC-MS and to evaluate its effectiveness against Staphylococcus aureus ATCC 25923. This research was carried out experimentally using a design featuring a control group. The extract was prepared via maceration with 95% ethanol. Chemical analysis was conducted using GC-MS, while the antibacterial properties were examined through the disk diffusion technique at concentrations of 0.5% w/v, 1% w/v, 2% w/v, 5% w/v, and 10% w/v. Data analysis was performed using one-way ANOVA along with Tukey’s post hoc test. The yield from the extract was 6.42%. The GC-MS analysis identified compounds including hexadecanoic acid, phytol, and piperlonguminine. The extract demonstrated inhibition of Staphylococcus aureus growth at all concentrations tested, with inhibition zones measuring from 6.65 to 12.72 mm. The statistical analysis indicated significant differences between the treatment groups (p < 0.001). In conclusion, the 95% ethanol extract of wild betel leaf (Piper aduncum L.) contains bioactive compounds and shows antibacterial effects against Staphylococcus aureus.